1991
DOI: 10.1126/science.1853202
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structures of β Peptide and Its Constituent Fragments: Relation to Amyloid Deposition

Abstract: The secondary structures in solution of the synthetic, naturally occurring, amyloid beta peptides, residues 1 to 42 [beta (1-42)] and beta (1-39), and related fragments, beta (1-28) and beta (29-42), have been studied by circular dichroism and two-dimensional nuclear magnetic resonance spectroscopy. In patients with Alzheimer's disease, extracellular amyloid plaque core is primarily composed of beta (1-42), whereas cerebrovascular amyloid contains the more soluble beta (1-39). In aqueous trifluoroethanol solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

48
508
1
5

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 545 publications
(562 citation statements)
references
References 46 publications
48
508
1
5
Order By: Relevance
“…The helical and β-sheet structure formations have been proposed to play crucial roles in the aggregation process of intrinsically disordered fibrillogenic proteins at the center of neurodegenerative diseases. 12,14,24,41 Within the N-terminal region (Met1-Lys60) of the wild-type and A30P mutant-type αS, we detect abundant α-helix formation at Ala19-Lys23 and 3 10 -helix formation at Val15-Ala18, Glu20-Thr22, Gly41-Thr44, and Thr54-Lys60 varying between 20% and 35% ( Figure 1). Interestingly, Gly7-Glu13, Val15-Ala17, Lys32-Val40, and Lys43-Gly47 adopt more prominent helical structure (α-helix or 3 10 -helix; up to 30%) in the structures of the A30P mutanttype than in those of the wild-type αS protein.…”
mentioning
confidence: 94%
“…The helical and β-sheet structure formations have been proposed to play crucial roles in the aggregation process of intrinsically disordered fibrillogenic proteins at the center of neurodegenerative diseases. 12,14,24,41 Within the N-terminal region (Met1-Lys60) of the wild-type and A30P mutant-type αS, we detect abundant α-helix formation at Ala19-Lys23 and 3 10 -helix formation at Val15-Ala18, Glu20-Thr22, Gly41-Thr44, and Thr54-Lys60 varying between 20% and 35% ( Figure 1). Interestingly, Gly7-Glu13, Val15-Ala17, Lys32-Val40, and Lys43-Gly47 adopt more prominent helical structure (α-helix or 3 10 -helix; up to 30%) in the structures of the A30P mutanttype than in those of the wild-type αS protein.…”
mentioning
confidence: 94%
“…Although the reasons for these deviations are unknown, they are believed to arise in part from differences in the aggregation states and the solution structures of the -peptides. The ability to produce the presumably neurotoxic, aggregated -sheet structure is dependent on many factors, particularly the peptide concentration, ionic strength, and solvent polarity (Barrow & Zagorski, 1991;Barrow et al, 1992;Hilbich et al, 1991;Shen et al, 1994;Snyder et al, 1994). For example, the aggregation rate is extremely rapid in aqueous acetonitrile solutions, such as those used for HPLC purification of the peptide (Shen & Murphy, 1995).…”
Section: Sample Preparationmentioning
confidence: 99%
“…The -(1-42) concentration was now 50 µM. Because the aggregational properties of the peptide rapidly increase below pH 7 (Fraser et al, 1991;Barrow & Zagorski, 1991;Burdick et al, 1992), the pH of the final solution was always immediately checked to ensure that it was above 7.1. In most cases, the pH remained at 7.2, indicating that a 14 mM phosphate buffer concentration was adequate to maintain the pH.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…This structure is modified with increasing temperature and pH so that at pH 1±4 or above 7 the peptides adopt a random coil structure but aggregate in a b-sheet conformation between pH 4 and 7. In contrast, the region 0 1 2 encompassing bA4[29±42] has been shown to adopt a b-strand conformation regardless of temperature and pH, and as such has been reported to direct the protein folding of the entire bA4 sequence to produce the b-pleated sheet structure found in amyloid deposits [7,8,15,16] In light of these observations, this study has demonstrated a unique C-terminal conformation within bA4[1±42], as defined using MoAb 3B9 which binds the GVV epitope. These results support the hypothesis that key residues within the C-terminal region of bA4[1±42] generate a unique peptide conformation which may be responsible for initiating the bA4 polymerization and amyloid fibril formation observed in the neuritic and diffuse plaques of AD.…”
Section: All Mice Immunized With Ba4[35±43]mentioning
confidence: 99%